PENERAPAN PRINSIP 5C DALAM PEMBERIAN KREDIT SEBAGAI PERLINDUNGAN BANK - Niniek Wahyuni (Faculty of Law, University of Dr. Soetomo, 2017)
Provision of credit to the Debtor's customers may result in loss or risk to the bank as the creditor if the underlying matters are ignored. To gain confidence and protect the interests of the bank, the bank must make a careful assessment of the nature, capability, capital, collateral, and business prospects of the debtor's customers, known as